DEVELOPMENT OF THREE TYPES OF ASSESSMENT IN LEARNING MATHEMATICS ON THE SYSTEM OF LINEAR EQUATIONS WITH THREE VARIABLES - Nadiayah, Ishomah; Shodikin, Ali (Universitas Sulawesi Barat, 2025)
This study aims to develop three types of assessments in mathematics learning for the Three Variable Linear Equation System material: initial, formative, and summative assessments. These three assessments are designed for use on a digital platform to enhance the efficiency of implementation and student involvement in the learning process. The study uses a Research and Development ( R&D ) approach with the ADDIE model consisting of five stages: analysis, design, development, implementation, and evaluation. The initial assessment in the form of a learning style questionnaire is distributed through Typeform to identify student learning characteristics. The formative assessment is designed in the form of an interactive quiz using the Nearpod application which includes multiple-choice questions. In the meantime, the summative evaluation is created as a context-based exam that gauges the knowledge, application, and reasoning dimensions. Four experts used Aiken's V test to validate the developed instrument, and Alpha Cronbach's reliability test was used to assess its dependability. With an Aiken's V > 0.80, the validation results demonstrate the instrument's high level of validity. The reliability test yields a moderately consistent Alpha Cronbach value of 0.45. The implementation's outcomes demonstrate that this technology-based evaluation can help identify student traits early on, offer feedback throughout the learning process, and measure learning success in a comprehensive way. Thus, creating this assessment could be a useful substitute for enhancing students' understanding of the Three Variable Linear Equation System.